2021
DOI: 10.1007/s12371-021-00558-8
|View full text |Cite
|
Sign up to set email alerts
|

The ABC Concept—Value Added to the Earth Heritage Interpretation?

Abstract: Holistic interpretation of Earth heritage is one of the most important tasks of UNESCO Global geoparks. The ABC (abiotic, biotic, and cultural interconnections) concept is a potential interpretive approach used in Earth heritage popularization through geotourism. Apart of the deeper understanding of this concept, this study explores the application of this concept in selected geoparks. The Colca and Volcanoes Andagua UNESCO Global Geopark (Peru) and Muroto UNESCO Global Geopark (Japan) served as a case study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…However, an important comment here is that these two UNESCObranded properties have different aims and hence, explorations of possible linkages will have to follow different paths. Whereas the primary aim of UNESCO World Heritage properties is ensure safeguarding of inherited values and (Dowling 2013;Pásková et al 2021). Here, winemaking process is presented as one among the ways to use available georesources.…”
Section: Discussionmentioning
confidence: 99%
“…However, an important comment here is that these two UNESCObranded properties have different aims and hence, explorations of possible linkages will have to follow different paths. Whereas the primary aim of UNESCO World Heritage properties is ensure safeguarding of inherited values and (Dowling 2013;Pásková et al 2021). Here, winemaking process is presented as one among the ways to use available georesources.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the alienation of man and nature, which is often the root of various environmental problems, can be overcome. The principle of integrated interpretation in the geopark area is also known as the ABC concept (abiotic-biotic-cultural interconnection), an interpretation approach used to popularize the Earth's heritage through geotourism [15,18].…”
Section: Geo-interpretationmentioning
confidence: 99%
“…Several specialists have argued that it is tied to cultural, historical, archaeological, and other categories of heritage. Particularly, Cárdenes et al [4] showed the connections between geological and industrial heritage and regional history; Ezquerro and Simón [5] related geoheritage to music; Gordon [6] put geoheritage into the context of cultural landscapes; Górska-Zabielska [7] demonstrated that a university's rock garden can be considered as geosite; Kubalíková [8] realized the cultural ecosystem services of geodiversity; Moroni et al [9] linked geological and archaeological heritage; Pásková et al [10] analyzed culture-geology interplay in geoparks; and Prosser [11] explained that quarry-based geosites establish cultural connections. Despite the accumulation of all these lines of evidence, two gaps are yet to be filled.…”
Section: Introductionmentioning
confidence: 99%